A survey of absenteeism on construction sites. Issue 4 (3rd July 2017) - Srour, F. Jordan; Srour, Issam; Lattouf, M. Ghayth
Abstract : Purpose: The construction industry is dynamic and often unregulated due to its complex, project-based nature. This makes the task of implementing human resource management (HRM) functions more difficult than in other economic sectors. This is particularly the case for developing countries which rely on a migrant, casual, and transient workforce. Despite offering flexibility, a transient workforce can lead to unpredictable rates of absenteeism and unsatisfactory productivity. This paper links HRM practices in the construction industry of the developing world to rates of absenteeism across three segments of the construction workforce – foremen, skilled workers, and unskilled workers. The paper aims to discuss these issues. Design/methodology/approach: A survey targeting 60 construction sites in Beirut, Lebanon form the basis of the analysis. Within each site, measures of absenteeism for foremen, skilled, and unskilled workers were solicited along with other data on HRM onsite. Findings: The results suggest a regression model for worker absenteeism based on tenure of work as well as the absenteeism of workers at the next hierarchical level onsite. Originality/value: This study is among the first to show a link between the mechanisms by which construction workers are employed (contract-based foremen vs daily/weekly labourers – both skilled and unskilled) and the rate of absenteeism seen onsite. Given the role of absenteeism in construction productivity, having a good understanding of the underlying causes of absenteeism is critical to the design of mitigating policies.